PENGARUH MODEL PEMBELAJARAN “SAVI (Somatik, Auditori, Visual, Intelektual)” TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI KELAS XI MIPA DI SMA ISLAM AL MAARIF SINGOSARI - Hesty Hyldania Azizah Hyldania Azizah; Ika Ratih Sulistiani; Indhra Musthofa (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This study discusses the impact of the SAVI learning model on the students learning outcomes in the PAI subject in the SMA Islam Al-Maarif Singosari XI MIPA class. This study is motivated by the phenomenon of using learning models in the PAI discipline, which are less efficient and affect students outcomes. The methodology employed in this study was quantitative, using a quasi-experimental format of a non-equivalent control group consisting of 54 students as the study sample. The data collection techniques used were lesson planning, testing and documentation. The results of this study show that the average score of students in the experimental class is higher than that in the control class, that is, the average score of the experimental class is 84.30 points, and average score of the control class is 69.63 points. Hypothesis test results using paired samples t-test showed that the value of sig (2-tailed) was less than 0.05 and was 0.000 (0.000<0.05), indicating that H0 rejected and Ha accepted. It can be concluded that the SAVI (Somatic, Auditory, Visual, Intellectual) subject in the Islamic Economics material for class XI MIPA at SMA Islam Al-Maarif Singosari for the 2021-2022 academic year.